USING INNOVATIVE NEW METHODS TO TEACH STUDENTS ABOUT HIV/AIDS - Ibragimova Dilfuzakhan Adkhamovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides for the prevention of HIV / AIDS among the population and youth, schoolchildren and students of colleges, institutes, improving medical culture and how to maintain their health.